Health and Academic Achievement New Findings - Bernal-Morales, Blandina (IntechOpen, 2021)
Due to the COVID-19 pandemic, the fields of health and education have been extensively revisited worldwide. This book addresses the importance of wellbeing in education. Health and Academic Achievement - New Findings provides recent reflections on the quality of informal learning environments in preschool-aged children, the acceptance of employing online education professionals, the mental health of teachers and students, and the challenges posed by current teaching and learning strategies during COVID-19. This book focuses on human behavior in health and education and will be of interest to readers in fields ranging from biology to sociology as well as readers interested in wellbeing and mental health.